Introduction to the Special Issue of “Relevant Tomorrow” Dedicated to Vilnius in the Nineteenth–Twenty-First Centuries (Relevant Tomorrow / Aktualu rytoj, 2023)
The introduction presents the special issue of the journal Relevant Tomorrow entitled “Europe. Capital. Transformations: Vilnius in the Nineteenth–Twenty-First Centuries,” dedicated to the 700th anniversary of Vilnius and the letters of Gediminas, celebrated in 2023. The chronological boundaries of this issue cover the last 200 years, during which Vilnius has experienced fundamental social, demographic and political changes: transforming from a provincial city of the Russian Empire, a German-occupied administrative center, a Polish provincial town, the capital of independent Republic of Lithuania and later, Soviet-occupied country to the capital of one of the EU countries. Using an interdisciplinary approach, the special issue considers and analyzes the changes related to Vilnius, their origins, current situation and future expectations. The articles are presented in thematic groups: 1) Places of memory and oblivion in Vilnius; 2) Multicultural Vilnius; 3) Vilnius as an administrative, economic, political, cultural and scientific center; 4) Urban and architectural development of Vilnius; 5) Vilnius in art; 6) Communicating Vilnius; 7) Visions of Vilnius’ future; and 8) Vilnius and nature. This special issue of Relevant Tomorrow is another contribution to the studies of Vilnius.
Keywords: nineteenth- and twenty-first-century Vilnius; Europe; capital; multicultural city; places of memory and oblivion; visions of Vilnius’ future; transformation